Use of antibiotic coated intramedullary nails in open tibia fractures: A European medical resource use and cost-effectiveness analysis. Issue 7 (July 2021) - Franz, D.; Raschke, M.; Giannoudis, P.V.; Leliveld, M.; Metsemakers, W.J.; Verhofstad, M.H.J.; Craig, J.A.; Shore, J.; Smith, A.; Muehlendyck, C.; Kerstan, M.; Fuchs, T.
Highlights: Using gentamicin-coated nail in patients at high risk of infection was associated with 75% lower rate of infection and cost savings (€477 - €3.263). Fewer infections, reduced inpatient days and re-operations may be potentially associated with use of antibiotic-coated implants. Results showed that usage of the gentamicin-coated nail in patients with severe open fractures can potentially lead to substantial cost savings. Abstract: Purpose: In patients with open tibial fractures, bone and wound infections are associated with an increased hospital length of stay and higher costs. The infection risk increases with the use of implants. Innovations to reduce this risk include antibiotic-coated implants. This study models whether the use of a gentamicin-coated intramedullary tibial nail is cost-effective for trauma centers managing patients with a high risk of infection. Efficacy: Absolute infection risk and relative risk reduction, by fracture grade, for antibiotic-coated nails compared to standard nails for patients with open tibial fractures were estimated based on the results of a meta-analysis, which assessed the additional benefit of locally-administered prophylactic antibiotics in open tibia fractures treated with implants. The observed efficacy of antibiotic-coated nails in reducing infections was applied in an economic model. Methods: The model compared infection rates, inpatient days, theatre usage and costs in high risk patients, with a Gustilo-Anderson (GA) grade III open fracture, for two patient cohorts from a trauma center perspective, with a 1-year time horizon. In one cohort all GAIII patients received a gentamicin-coated nail whilst GAI and GAII patients received a standard nail. All patients in the comparator cohort received a standard nail. Four European trauma centers provided patient-level data (n=193) on inpatient days, procedures and related costs for patients with and without infections. Results: Using the gentamicin-coated nail in patients at high risk of infection (GAIII) was associated with 75% lower rate of infection and cost savings (€477 - €3.263) for all included centers; the higher cost of the implant was offset by savings from fewer infections, inpatient days (-26%) and re-operations (-10%). This result was confirmed by extensive sensitivity analyses. Conclusions: Analyses demonstrated that infection rates and total costs for in-hospital treatment could be potentially reduced by 75% and up to 15% respectively, by using a gentamicin-coated nail in patients at high risk of infection. Fewer infections, reduced inpatient days and re-operations may be potentially associated with use of antibiotic-coated implants. Results are sensitive to the underlying infection risk, with greatest efficacy and cost-savings when the coated implant is used in high risk patients.